2006
DOI: 10.1111/j.1348-0421.2006.tb03824.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Mice Susceptibility to Infection with Listeria monocytogenes by the Treatment of Morphine

Abstract: Abstract:The effect of morphine on the susceptibility of BALB/c mice to diarrheagenic Escherichia coli, Shigella flexneri, Listeria monocytogenes, Salmonella Enteritidis, Yersinia enterocolitica, was examined via the intraperitoneal inoculation. Morphine treatment increased the susceptibility to S. Enteritidis and L. monocytogenes, resulting in bacteremia and central nervous system (CNS) invasion (for L. monocytogenes), while the infection with other bacteria did not show the systemic dissemination in the morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Experimental animal studies showed that opioid treatment causes increased susceptibility and mortality to various bacterial infections, including S. pneumoniae [87,88], K. pneumoniae [86], acute Toxoplasma gondii [11], oral Salmonella typhimurium [24], Candida albicans [81], Acinetobacter baumannii [40], S. aureus [38], and Listeria monocytogenes [2]. Although opiate addiction has been identified as a risk factor for clinical tuberculosis [17], an in vitro infection study, contrary to other bacterial infection studies, showed that morphine stimulated the phagocytosis of M. tuberculosis by human microglial cells, the resident macrophages of the brain.…”
Section: Opiate Abuse Affects Bacterial Infection In Animal Modelsmentioning
confidence: 99%
“…Experimental animal studies showed that opioid treatment causes increased susceptibility and mortality to various bacterial infections, including S. pneumoniae [87,88], K. pneumoniae [86], acute Toxoplasma gondii [11], oral Salmonella typhimurium [24], Candida albicans [81], Acinetobacter baumannii [40], S. aureus [38], and Listeria monocytogenes [2]. Although opiate addiction has been identified as a risk factor for clinical tuberculosis [17], an in vitro infection study, contrary to other bacterial infection studies, showed that morphine stimulated the phagocytosis of M. tuberculosis by human microglial cells, the resident macrophages of the brain.…”
Section: Opiate Abuse Affects Bacterial Infection In Animal Modelsmentioning
confidence: 99%
“…In mice, chronic morphine has been shown to modulate bacterial killing by inhibition of NO release (Bhaskaran et al 2007;Menzebach et al 2004). Our laboratory's previous data and several other studies indicate that chronic morphine, by inhibition of NO release, increases susceptibility to bacterial infection, resulting in bacteremia and bacterial invasion of the CNS (Asakura et al 2006;Bhaskaran et al 2007;Wang et al 2005). A recent study by Singh and Singal (2007), notes that morphine administration has a dosedependent biphasic modulation in Leishmania donovani infected mice and peritoneal macrophages in vitro, via a NO-dependent mechanism.…”
Section: Morphine Modulation Of Macrophage Phagocytosismentioning
confidence: 71%
“…There is a substantial experimental literature documenting the immunosuppressive effects of opioids at the receptor (Beagles et al 2004;Tegeder and Geisslinger 2004) cell, (Hatsukari et al 2006), organ , and organism (Asakura et al 2006) level. Since infection is the most common consequence of immunosuppression, most studies have concentrated on one of three infectious models: (1) the effects of chronic opioid exposure on the severity or lethality of a new infectious or lipopolysaccharide (LPS) challenge (MacFarlane et al 2000;Ocasio et al 2004); (2) the effect of initiating opioid therapy in a previously infected animal (Chao et al 1990); or (3) the course of an infection induced in an animal previously made tolerant to opioids and then acutely withdrawn during the infection (Feng et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since infection is the most common consequence of immunosuppression, most studies have concentrated on one of three infectious models: (1) the effects of chronic opioid exposure on the severity or lethality of a new infectious or lipopolysaccharide (LPS) challenge (MacFarlane et al 2000;Ocasio et al 2004); (2) the effect of initiating opioid therapy in a previously infected animal (Chao et al 1990); or (3) the course of an infection induced in an animal previously made tolerant to opioids and then acutely withdrawn during the infection (Feng et al 2005). Generally, opioids have been found to have deleterious effects in all three infectious paradigms and across a broad range of pathogenic microorganisms: invasive intracellular (Asakura et al 2006), extracellular , and enteric bacteria, (Hilburger et al 1997), mycobacteria (Olin et al 2007), protozoans (Chao et al 1990), yeasts (Di Francesco et al 1997), and viruses (Hu et al 2005). Table 1 summarizes experimental animal studies that have reported mortality ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation